Exceptional combination of soft magnetic and mechanical properties in a heterostructured high-entropy composite. (June 2019) - Fu, Zhiqiang; MacDonald, Benjamin E.; Dupuy, Alexander D.; Wang, Xin; Monson, Todd C.; Delaney, Robert E.; Pearce, Charles J.; Hu, Ke; Jiang, Zhenfei; Zhou, Yizhang; Schoenung, Julie M.; Chen, Weiping; et al.
Graphical abstract: Highlights: Heterogeneous grain sizes in high entropy alloys via in-situ formation of TiC particles. TiC, unalloyed Fe and localized overheating facilitate heterogeneous microstructure. Dramatic enhancement in tensile yield strength with a negligible loss in fracture strain. Soft magnetic properties enhanced due to a remarkable improvement in coercivity. Heterogeneous microstructure and TiC activate multiple strengthening mechanisms. Abstract: High-entropy alloys (HEAs) represent a class of metallic materials that provide new pathways to attain heretofore unachievable combinations of physical and mechanical properties. However, published studies are focused on either physical properties or mechanical properties, rather than combinations thereof. Here, a "heterogeneous microstructure" was designed, via in situ formation of nano-sized TiC particles, to achieve enhancements in both mechanical and soft magnetic properties in a FeNiCo-based HEA. When compared to the HEA matrix counterpart material, a dramatic enhancement in tensile yield strength, with a negligible loss in fracture strain was obtained in the heterostructured high-entropy composite (HS-HEC). In addition, its soft magnetic properties were also enhanced as evidenced by a remarkable improvement in coercivity. Our results confirm that the HS-HEC displays a heretofore unattainable combination of soft magnetic and mechanical performance when compared to those of previously studied HEAs. This exceptional combination of soft magnetic and mechanical properties was primarily attributed to the presence of a heterogeneous microstructure containing dispersed TiC particles. The results presented here validate the hypothesis that a heterogeneous microstructure provides a powerful strategy to tailor the soft magnetic and mechanical response of HEAs.